Quality Assurance Systems in Food Production - Paździor , Magdalena (Studia Oeconomica Posnaniensia, 2016)
Food production is the subject of numerous systemic solutions within the scope of health quality assurance. A common purpose for all the pro-quality actions taken in a production organisation is constituted by the achievement of the products' quality level consistent with the preferences of the customers. Health quality of food is closely related to the quality of its materials and semi-finished products from so-called primary production. Food business operators must comply with the requirements of material protection from possible contamination and with the relevant EU and national legislation referring to hazard control in the area of primary production. This paper includes an analysis of systems supporting the organisations manufacturing primary products in their efforts to provide their proper health quality. Production organisations operating in the area of food primary production have usually the obligation to implement the quality assurance systems ensuring the health quality of food offered to the consumers. In addition, the paper identifies the EU and domestic legislation providing the obligation of applying the health quality of food' assurance systems in the primary production implemented on the level of farms. It outlines regulations applicable to the primary production and related actions for the benefit of improved food safety.